The Effect of Information Asymmetry and Individual Morality on Accounting Fraud Moderated by Accounting Rule Compliance - Humaeroh, Putri Ummi; Ariza, Fitri (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to test, analyze, and provide empirical evidence regarding the effect of information asymmetry and individual morality on accounting fraud, with accounting rule compliance as a moderating variable, on high school teachers majoring in accounting in Bekasi regency. Design/methodology/approach – This research uses quantitative methodology with correlational approach. A total of 30 questionnaires, each containing 33 statements, were distributed to teachers teaching accounting subject areas, and all 30 responses were received. Data analysis was conducted using PLS-SEM version 3.0 to obtain the research results. Findings – The findings indicate that information asymmetry has a positive and significant effect on accounting fraud, while individual morality has a negative and insignificant effect accounting fraud. Accounting rule compliance does not significantly moderate the relationship between information asymmetry and accounting fraud, not does it significantly moderate the relationship between individual morality and accounting fraud. Research limitations/implications – This study is limited by the relatively small sample size of 30 respondents. Which may have an impact on the generalizability of the findings. Future research can expand the sample or explore additional variables to better understand the factors that influence accounting fraud in various context.